2017
DOI: 10.1002/pamm.201710010
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Multiple Body Models for Brake Squeal

Abstract: Brake squeal is a self-excited vibration with initially inclining amplitude reaching a limit cycle due to nonlinearities. For a proper simulation of this behavior, it is necessary to know the origin and the influence of the brake system's nonlinearities. It is generally known, that nonlinearities are inherent to the joints [1, 2], complex friction laws [3] and the friction material of the system [4][5][6]. In this work, the influence of friction material and shim nonlinearities on the existence of a limit cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Several attempts have been made in the past years to describe these effects and to investigate the resulting effects, e.g. [12][13][14][15][16][17][18][19]. These attempts are essential for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts have been made in the past years to describe these effects and to investigate the resulting effects, e.g. [12][13][14][15][16][17][18][19]. These attempts are essential for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…In this consideration, nonlinearities limit the increasing oscillation caused by self-excitation, which finally ends in a limit cycle [6,11]. Therefore, nonlinearities resulting in the limitation of the increasing vibration are essential if the "real" brake squeal, i.e., the limit cycle, should be obtained in frequency, amplitude and sound radiation, and therefore, these nonlinearities are considered by a number of authors and publications [12][13][14][15]. For example, in [6] it is shown that the mode shape with the largest positive eigenvalue is not necessarily the one resulting in the limit cycle and therefore the squeal event.…”
Section: Introductionmentioning
confidence: 99%
“…Both the damping term, caused by the vibrations of the transverse components of the relative velocities between the pads and the disk, and the gyroscopic terms affect the stability of the system and they both depend on the macroscopic angular velocity of the disk [5]. Besides models with continua, models with wobbling disk can also capture these terms; therefore, some models have been developed in this way to study the mechanism of brake squeal: minimal model with 2 DOFs [6], 2-DOF model with in-plane vibration of the pads [7], 6-DOF model [5] and 8-DOF model [8]. In those studies, a specialized commercial software called Autolev [9] was required to obtain the final form of the equations of motion, which is quite inconvenient for further generalization.…”
Section: Introductionmentioning
confidence: 99%